Environmental Concerns in Race to Approve 'Second Wave' of LNG Export Facilities. Issue 9 (14th April 2019) - Ensor, James; Daly, Matthew
Abstract : Liquefied natural gas (LNG) has fast become a much‐discussed fuel trend in the energy industry, and the United States is poised to become a major world player exporting LNG. Building the infrastructure required to export US‐made LNG takes years and requires approval from various federal and state regulatory bodies. With the administration and federal agencies pursuing an "energy dominance" strategy to become a world‐leading fossil fuel exporter, the responsibility for ensuring export facilities are environmentally sound falls to the states. An adequate environmental cost and economic benefit framework needs to be established to determine whether these facilities are in the public interest, and it's an open question as to who will create that framework